Definicja przysłowia w wybranych opracowaniach francuskich, niemieckich i polskich oraz próba konfrontatywnej analizy problemu - Zakrzewski, Paweł (Acta Universitatis Lodziensis. Folia Linguistica, 2002)
In the paper Definition of proverb in selected French, German and Polish papers and an attempt of contrastive analysis of the issue, there is an attempt of creating a concise and clear definition of proverb, by comparing the definitions of different authors. Thus, proverb is a short and autonomous expression, with normative and didactic message, transferred metaphorically. In addition, the paper describes briefly the current results of sociolinguistic research, studying the relations between languages and language communities, as well as analysing similarities and differences between languages. Moreover, there are presented some results of a practical comparative analysis of a collection of French, German and Polish proverbs. It is shown that dog and cat are the most frequent animals in analysed examples, and that the “ statistical proverb animal” is a mammal. As far as their normative message is concerned, they concern generally the norms defending dignity and justice. Finally, it is concluded that there are practically no differences in treating the issue between the French, German and Polish societies.